1
$\begingroup$

I'm stuck trying to understand the first paragraph of this proof.

Let $X\rightarrow Y$ be a dominant morphism of affine varieties and denote $B=k[X]$,$A=k[Y]$. Assume there exists $b\in B$ such that $B=A[b]$, so $B=A[T]/I$ for some ideal $I$. Pick $x\in X$ and let $\epsilon:A\rightarrow k$ be the homomorphism defined by $\phi(x)$. Extend it to a homomorphism $\epsilon:A[T]\rightarrow k[T]$.

He claims that if $ \epsilon(I)=0$, then $k[\phi^{-1}(\phi(x))]=k[T]$, but I don't quite see it...

$\endgroup$
1
$\begingroup$

Let $\varphi:A\rightarrow B$ be the morphism associated to $\phi:X\rightarrow Y$ and let $\pi:A[T]\rightarrow B$ be the surjection such that $\varphi=\pi\circ\iota$, where $\iota:A\rightarrow A[T]$ is the inclusion map. Let $\tilde{\epsilon}:A[T]\rightarrow K[T]$ be the extension of $\epsilon$ which is a surjection whose kernel is the ideal of $A[T]$ generated by $\ker(\epsilon)$. The hypothesis on $\tilde{\epsilon}$ implies that there exists a surjection $\eta:B\rightarrow k[T]$ such that $\eta\circ\pi=\tilde{\epsilon}$.

Note that $\mathfrak{m}:=\ker(\epsilon)=\{f\in A:f(\phi(x))=0\}$ is the ideal of $\{\phi(x)\}$. Therefore $\varphi(\mathfrak{m})$ generates an ideal ( $\varphi(\mathfrak{m})B$ ) whose zero zet is $\phi^{-1}(\phi(x))$ (in fact $Z(\varphi(\mathfrak{m}))=\{x'\in X:\varphi(f)(x')=0\ \forall f\in\mathfrak{m}\}=\{x'\in X:f(\phi(x'))=0\ \forall f\in\mathfrak{m}\}=\phi^{-1}(Z(\mathfrak{m}))$. ).

Then it is enough to prove that $B/\varphi(\mathfrak{m})B\cong k[T]$. Now, $\ker(\eta)=\pi(\ker(\tilde{\epsilon}))=\pi((\ker(\epsilon)))=(\varphi(\ker(\epsilon)))=\varphi(\mathfrak{m})B$ and therefore $\eta$ induces an isomorphism $B/\varphi(\mathfrak{m})B\cong k[T]$.

Sorry if this is too long!.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.